PSXII-13 Blood flow parameters in ovine fetuses from different sires. (8th October 2021) - Checura, Celina M; Atkinson, Katherine; Boulos, Natalie; Crowfoot, Emma; Friend, Hannah; Jackson, Sophia; Lubowicki, Shelby; Silva, Camila; Bridges, William; Duckett, Susan K; Walker, Eric
Abstract: Placental and fetal development are influenced by paternal genes. Doppler ultrasonography was performed on pregnant ewes to examine the effect of sire on fetal and placental blood flow parameters. Twenty Suffolk ewes were randomly assigned to either a Suffolk ram or a Texel ram. Only ewes carrying twins were used for the study. Ultrasound exams were performed at 60, 90, and 120 (± 3) days post-breeding. Umbilical artery and fetal aorta blood-flow velocities, and aorta vessel diameter were measured. Blood flow velocities were used to calculate the resistance index (RI), which was used for statistical analysis (Glimmix, SAS). Gestational age and weight at birth were recorded. There were 5 Suffolk x Suffolk (SxS) and 6 Suffolk x Texel (SxT) ewes carrying twins to term. For umbilical artery RI, there was no significant (P < 0.05) effect of breed; there was significant effect of time (0.89 ± 0.03 a ; 0.63 ± 0.03 b ; 0.59 ± 0.03 b LSM ± SE for days 60, 90, and 120 respectively); and there was no interaction. For aorta RI, there was no significant effect of breed; there was significant effect of time (0.73 ± 0.03 a ; 0.67 ± 0.03 ab ; 0.63 ± 0.03 b for days 60, 90, and 120 respectively); and there was no interaction. For aorta diameter, the effect of breed approached significance (P = 0.054), SxS had a larger average diameter (0.50 ± 0.02 cm) than SxT (0.45 ± 0.01 cm); there was significant effect of time (0.24 ± 0.03 a ; 0.46 ± 0.02 b ; 0.72 ± 0.02 c cm for days 60; 90; and 120 respectively); and there was no interaction. There were no significant differences between sires for weight or gestational age at birth. The results correspond with the changes in fetal and placental vascular resistance over time; however, further research is needed to expand our knowledge on the effect of sire.